Depiction of Brahmani seated upon a pedestal - Temples of India Project Team (Jio Institute, 2024)
Adorning the lateral side of the antarala’s (vestibule) shikhara (superstructure), Brahmani is depicted seated upon a pedestal, and with four arms, each bearing attributes. In her upper right hand, she holds a shruka (sacrificial ladle) and her upper left-hand holds a pustaka (sacred text). Her lower left-hand holds a phala (fruit), signifying abundance and nourishment, while her lower right hand is held in the varada hasta gesture, adorned with an akshamala (rosary).